Synthesis method of oxytetracycline-containing organic sulfur-iron micron column and method for applying oxytetracycline-containing organic sulfur-iron micron column to sewage treatment

By synthesizing organic sulfur iron micron columns containing oxytetracycline, the problems of uneven morphology and low chromium removal efficiency of iron-sulfur materials under mild conditions in the existing technology are solved, and the effect of efficient removal of hexavalent chromium is achieved. It is applicable to a wide pH range and has no secondary pollution.

CN120774969APending Publication Date: 2025-10-14ZHONGKAI UNIV OF AGRI & ENG +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410416269.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

When treating chromium-containing wastewater, existing technologies find it difficult to synthesize iron-sulfur materials with uniform morphology under mild conditions. In addition, the efficiency of complex breaking and chromium removal under the action of an electric field is limited, the applicable pH range is narrow, and hexavalent chromium cannot be effectively removed.

Method used

Using organic sulfur iron micron columns containing oxytetracycline, nano-sized KFeS2 rods are synthesized under mild conditions, and the pH is adjusted to 3-7.0 under stirring to convert them into micron-sized organic iron sulfur rod-shaped materials, thereby enhancing their complex breaking ability and chromium removal efficiency under the action of an electric field.

Benefits of technology

The decomplexation and chromium removal efficiency of organic chromium are significantly improved, the applicable pH range is expanded, and the synthesis process is simple, the material morphology is uniform, and no secondary waste is generated during the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120774969A_ABST
    Figure CN120774969A_ABST
Patent Text Reader

Abstract

The invention provides an oxytetracycline-containing organic pyrite micron column and a synthesis method thereof, the oxytetracycline-containing organic pyrite micron column is prepared by preparing a solution containing potassium salt and oxytetracycline, adding ferrous salt and KFeS2 and reacting under stirring, an organic pyrite material is synthesized under a mild condition, the morphology is uniform, and the preparation method is simple. The organic sulfur iron micron column shows the reduction coordination characteristic of an oxytetracycline-Fe / S ligand, the performance stability of a Fe / S structural material is enhanced, the applicable pH range is wide, and the complexing breaking and chromium removal efficiency on organic chromium under the action of an electric field is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental protection, and in particular relates to an organic sulfur iron micron column containing oxytetracycline, a synthesis method thereof, and an application thereof in the treatment of wastewater or sewage containing heavy metals (ions). Background Art

[0002] In the field of sewage treatment and waste resource utilization, chromium-containing wastewater has always been a difficult and important issue. The treatment of chromium-containing wastewater generally includes the following directions: (1) adding sodium pyrosulfate or sodium sulfite, adjusting the pH, and then adding a coagulant to remove chromium by co-precipitation; (2) adding excessive amounts of ferrous salts to remove chromium by reduction co-precipitation; (3) adding adsorbents and using the functional groups on the adsorbent surface to achieve chromium immobilization or reduction fixation. This type of method generally targets the reduction of hexavalent chromium, and after generating trivalent chromium, the pH is controlled or the liquid / solid interface is hydrolyzed to generate hydroxide colloid, which is then removed in the form of precipitation. The use of the electro-Fenton process to remove chromium mainly focuses on the decomposition and precipitation of organic trivalent chromium.

[0003] Some iron-sulfur columnar materials used in the reported electro-Fenton process have crystal structures that show pyrite, chalcopyrite, or one-dimensional linear materials (such as KFeS2). In addition, iron-containing MOF materials are mostly synthesized using dimethylformamide as a solvent under closed hydrothermal conditions exceeding 100°C. Although the morphology of this type of iron-containing MOF material is diverse, with some showing quadrangular prisms, the material generally does not contain sulfur and oxytetracycline groups. To date, there have been no reports on the use of oxytetracycline in the synthesis of iron-sulfur micro-columns and their use in the treatment of chromium-containing wastewater. Summary of the Invention

[0004] To solve the above problems, the present invention provides an organic sulfur iron micron column containing oxytetracycline and a synthesis method thereof. The organic sulfur iron material is synthesized under mild conditions and has a uniform morphology. The organic sulfur iron micron column exhibits the reducing coordination characteristics of oxytetracycline-Fe / S ligand, enhances the performance stability of the Fe / S structural material, significantly enhances the decomplexation and chromium removal efficiency of organic chromium under the action of an electric field, has a wide applicable pH range, and has broad application prospects in the field of environmental protection.

[0005] The object of the present invention is to provide an organic sulfur iron micron column containing oxytetracycline, which has a side length of 1-100 μm, preferably 5-50 μm, and a length of 10-1000 μm, preferably 20-800 μm.

[0006] The synthesis of the organic sulfur iron micron column containing oxytetracycline comprises the following steps:

[0007] Step 1: prepare a solution containing potassium salt and oxytetracycline.

[0008] Step 2: Use of KFeS2

[0009] Step 3: Synthesize and collect micron columns.

[0010] In step 1,

[0011] Prepare a solution containing 10-30% potassium salt and 10-50g / L oxytetracycline; the potassium salt is potassium halide, preferably potassium chloride,

[0012] The solution is heated to 30-80° C., and then an inert gas is introduced into the solution for aeration; a ferrous salt, preferably ferrous chloride, is added to the resulting solution, and the ferrous concentration is adjusted to 1.0-3 g / L.

[0013] In step 2, KFeS2 rods, preferably nano KFeS2 rods, are added to the solution, and then the pH value is adjusted to be in the range of 3-7.0, preferably 5-6.8.

[0014] In step 3, stirring is continued for 3-6 hours, and then filtered and dried to obtain a micron column.

[0015] Another object of the present invention is to provide the use of organic sulfur iron micron column containing oxytetracycline prepared by the above method for water treatment, especially for treating wastewater or sewage containing heavy metal (such as chromium) ions.

[0016] The organic oxytetracycline-containing iron-sulfur micron column provided by the present invention, its synthesis method and application, have the following beneficial effects:

[0017] Compared with the reported Fe / S materials, the organic sulfur iron micron column containing oxytetracycline provided by the present invention exhibits the reduction coordination characteristics of oxytetracycline-Fe / S ligands, and can significantly enhance the efficiency of organic chromium decomposition and chromium removal under the action of an electric field;

[0018] The nanometer-sized rod-shaped Fe / S material is in situ converted into a micrometer-sized organic iron-sulfur rod-shaped material, which enhances the performance stability of the Fe / S structural material and has a wider applicable pH range;

[0019] The micron column synthesis method provided by the present invention synthesizes an organic ferrosulfide material under mild conditions. The material has uniform morphology and a simple preparation process. The solution used can be recycled and no secondary waste is generated. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 1. The morphology of the KFeS2 rod prepared in Example 1 is shown;

[0021] Figure 2 1. The crystalline structure of the KFeS2 rod prepared in Example 1 is shown;

[0022] Figure 3 shows the morphology of the micron column prepared in Example 1;

[0023] Figure 4 shows the crystal phase structure of the micron column prepared in Example 1;

[0024] Figure 5 Shown is a morphology diagram of the product of Comparative Example 1;

[0025] Figure 6 The crystalline structure of the product of Comparative Example 1 is shown;

[0026] Figure 7 Shown is a morphology diagram of the product of Comparative Example 2;

[0027] Figure 8 The crystalline structure of the product of Comparative Example 2 is shown;

[0028] Figure 9 Shown is a morphology diagram of the product of Comparative Example 3;

[0029] Figure 10 The removal results after treatment with different reagents / conditions in the application examples are shown. DETAILED DESCRIPTION

[0030] The present invention will be described in detail below through specific embodiments, and the features and advantages of the present invention will become clearer and more distinct with these descriptions.

[0031] According to the first aspect of the present invention, an organic sulfur iron micron column containing oxytetracycline and a synthesis method thereof are provided. The organic sulfur iron micron column is also called a micron rod, and its side length is 1-100 μm and its length is 10-1000 μm, preferably the side length is 5-50 μm and the length is 20-800 μm, more preferably the side length is 10-15 μm and the length is 50-500 μm.

[0032] According to the present invention, the organic sulfur iron microrods are synthesized or prepared by a method comprising the following steps:

[0033] Step 1: Prepare a solution containing potassium salt and oxytetracycline

[0034] Prepare a solution containing 10-30% potassium salt and 10-50g / L oxytetracycline, preferably a solution containing 12-20% potassium salt and 20-40g / L oxytetracycline.

[0035] In the present invention, the potassium salt can be any inorganic potassium salt, preferably potassium halide, more preferably potassium chloride.

[0036] According to the present invention, the solution needs to be deoxygenated, for example, the solution is heated to 30-80°C, preferably 50-60°C, and then an inert gas, preferably nitrogen, is introduced into the solution for aeration to achieve deoxygenation.

[0037] According to a more preferred embodiment, a ferrous salt, preferably a ferrous inorganic acid salt, more preferably a ferrous halide, such as ferrous chloride, is also added to the resulting solution, and the ferrous concentration is adjusted to 1.0-3 g / L, preferably 1.5-2 g / L.

[0038] Step 2, use of KFeS2

[0039] KFeS2 rods are added to the above solution, and stirring is started.

[0040] In the present application, the KFeS2 rods are preferably nanorods, which are one-dimensional linear materials, and can be commercially available or prepared in situ from iron salts and potassium sulfide according to known methods. The obtained KFeS2 rods have a diameter of tens to hundreds of nanometers and a length of about 0.5-100 microns, preferably 1-10 microns.

[0041] According to a preferred embodiment of the present application, after the addition of KFeS2 rods, the pH value should be adjusted to obtain a suitable crystal growth environment.

[0042] In the present application, inorganic acids or inorganic bases can be used to adjust the pH value, and in order not to introduce new ions, hydrochloric acid or potassium hydroxide is preferably used for adjustment; but more preferably, FeCl2 is used to adjust the pH value, which is a strong acid-weak base salt, and at the same time will not introduce additional ions into the system, for example, by adding a certain concentration, such as 5-20%, preferably 8-15%, of FeCl2 solution to control the pH value in the range of 3-7.0, preferably 5-6.8, more preferably 5.5-6.5.

[0043] Step 3, synthesis and collection of micropillars

[0044] After continuous stirring for 3-6 hours, the solid is collected by filtration and vacuum dried to obtain micropillars with a side length of 10-15 microns and a length of 50-500 microns.

[0045] According to another aspect of the present application, the use of the micropillars is also provided, which is used in the field of environmental protection, especially in the utilization of waste resources and wastewater treatment, especially in the treatment of wastewater containing heavy metal ions such as chromium.

[0046] The micropillar material of the present application is dispersed in wastewater or sewage containing heavy metal ions, and chromium and other heavy metals in the wastewater can be efficiently removed within tens of minutes to several hours.

[0047] In the application process, it can be carried out at room temperature, and the pH value is preferably adjusted to be non-strongly acidic and strongly alkaline, for example, the pH value is between 2-12, preferably between 3-10.

[0048] According to the present application, potassium hydroxide or hydrochloric acid is preferably used to adjust the pH value, so that no additional anions and cations are introduced except potassium and chlorine.

[0049] Example 1

[0050] Prepare a 24% KCl aqueous solution, add an equal volume of a 40g / L oxytetracycline aqueous solution thereto, mix well, and heat to 50°C; place the solution in a glove box, aerate with nitrogen, and complete deoxygenation; add ferrous chloride to the mixture to a concentration of 1.5g / L.

[0051] KFeS2 rods are prepared from FeCl3 and K2S, and their morphology is as follows Figure 1 As shown, the diameter of the KFeS2 rod is about 200nm and the length is about 5 microns. Its crystal structure is as follows Figure 2 shown.

[0052] According to stoichiometric measurements, the prepared KFeS2 rods were added to the mixture at a weight ratio of 0.8 to oxytetracycline concentration, and stirring was initiated at 120 rpm. During this process, an online pH control was activated and set to 6. After stirring for 3 hours, stirring and heating were stopped.

[0053] Filter through filter cloth, freeze, and dry to obtain micron column products with a side length of about 10 microns and a length between 50-400 microns. Figure 3 As shown, the scale bar on the left is 50 μm, and the scale bar on the right is 10 μm; its crystal structure is as follows Figure 4 shown.

[0054] Depend on Figure 3 and Figure 4 It can be seen that the generated micron columns have relatively regular sizes, smooth surfaces and few impurities.

[0055] Comparative Example 1

[0056] The preparation was carried out according to the method of Example 1, except that tetracycline hydrochloride was used instead of oxytetracycline. Irregular flocs were generated after the reaction, and their morphology was as follows. Figure 5 Its crystal structure is shown in Figure 6 .

[0057] Comparative Example 2

[0058] The preparation was carried out according to the method of Example 1, except that ferrous iron was not used to control the pH. As a result, a small amount of micron columns were obtained, and the column surface was rough and contained a large amount of flocs. Its morphology was as follows: Figure 7 As shown, the scale bar on the left is 50 μm, and the scale bar on the right is 10 μm; its crystal structure is as follows Figure 8 shown.

[0059] Comparative Example 3

[0060] The preparation was carried out according to the method of Example 1, except that no ferrous salt was used and no ferrous salt was used to control the pH. As a result, the amount of crystals generated was small and the surface was rough, making it difficult to determine the crystal structure. The morphology was as follows: Figure 9 As shown, the scale bar in the left figure is 100 μm, and the scale bar in the right figure is 50 μm.

[0061] Application Examples

[0062] Chromium-containing wastewater was obtained from a chemical plant, with a Cr concentration of 380 mg / L, a citrate concentration of 415 mg / L, and a salt content of 8%, which is high-salt organic wastewater.

[0063] 3.5 g / L of the micronized column prepared in Example 1 was added to the wastewater, with the persulfate dosage controlled at 20 mM. The electric field (current set at 100 mA, voltage at 20 V, and electrode spacing of 2 cm) and stirring device were activated. The treatment was continued for 30 minutes, after which stirring was stopped and the electric field was turned off. The residual chromium concentration was measured to be less than 0.5 mg / L.

[0064] For comparison, the above chromium-containing wastewater was treated with KFeS2, pyrite, chalcopyrite, commercial Fe-MOF, and ferrous salts without using an electric field, and was also treated with a pure electric field. The treatment results are summarized in Figure 10 middle.

[0065] As shown in the figure, compared to a 100% removal rate using micron-sized pillars, the total chromium removal rates for KFeS2 (approximately 44% removal efficiency), pyrite (approximately 23% removal efficiency), chalcopyrite (approximately 22% removal efficiency), commercially available Fe-MOF (approximately 26% removal efficiency), and ferrous salts (approximately 17% removal efficiency) were less than 50%. This shows that, under the same conditions, the pillars provided by the present invention offer superior removal rates to those of micron-sized iron-sulfur minerals and ferrous salts.

[0066] The present invention has been described in detail above with reference to specific embodiments and / or exemplary examples and the accompanying drawings. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will appreciate that various equivalent substitutions, modifications, or improvements may be made to the technical solutions and implementations of the present invention without departing from the spirit and scope of the present invention, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be determined by the appended claims.

Claims

1. An organic sulfur iron micron column containing oxytetracycline, having a side length of 1-100 μm and a length of 10-1000 μm, preferably a side length of 5-50 μm and a length of 20-800 μm.

2. A method for synthesizing an organic ferrous sulfur micron column containing oxytetracycline, characterized in that: The method comprises the following steps: Step 1: prepare a solution containing potassium salt and oxytetracycline. Step 2: Use of KFeS2 Step 3: Synthesize and collect micron columns.

3. The method according to claim 2, characterized in that In step 1, Prepare a solution containing 10-30%, preferably 12-20%, of potassium salt and 10-50g / L, preferably 20-40g / L of oxytetracycline. The potassium salt is potassium halide, preferably potassium chloride.

4. The method according to claim 2 or 3, characterized in that In step 1, The solution is heated to 30-80° C., preferably 50-60° C., and then an inert gas, preferably nitrogen, is introduced into the solution for aeration.

5. The method according to any one of claims 2 to 4, characterized in that In step 1, Add ferrous salt, preferably ferrous halide, such as ferrous chloride, to the obtained solution, and adjust the ferrous concentration to 1.0-3 g / L, preferably 1.5-2 g / L.

6. The method according to any one of claims 2 to 5, characterized in that In step 2, KFeS2 rods, preferably nano KFeS2 rods, are added to the solution, with a diameter of tens to hundreds of nanometers and a length of about 0.5-100 microns, preferably 1 to 10 microns.

7. The method according to claim 6, characterized in that In step 2, After adding the KFeS2 rods, the pH value is adjusted to be in the range of 3-7.0, preferably 5-6.8, more preferably 5.5-6.

5.

8. The method according to any one of claims 2 to 7, characterized in that In step 3, stirring is continued for 3-6 hours, and then filtered and dried to obtain a micron column.

9. Use of the organic sulfur iron micron column containing oxytetracycline according to claim 1 for water treatment, especially for treating wastewater or sewage containing heavy metal (such as chromium) ions.

10. The use according to claim 9, wherein the micron column material is dispersed in wastewater or sewage containing heavy metal ions, and the pH value is adjusted to 2-12, preferably 3-10.

Citation Information

Cited By

  • A potassium ferrosulfide material loaded on biochar and its application in removing pollutants

    CN122352315A